Rationale for the Use of Extracorporeal Shock Wave Therapy in the Treatment of Delayed Union of Bone Fractures and Pseudoarthrosis - Hertsen, H.I.; Remeniuk, Yu.K.; Bilonozhkin, H.H.; Sikorska, M.V. (TERRA ORTHOPAEDICA, 2022)
Relevance. Violation of bone formation processes continues to occupy a relatively high level, reaching 2.7-27.1%, so the search for new methods for their treatment and prevention remains relevant. One of these methods is extracorporeal shock wave therapy. Views on the influence of the extracorporeal shock wave therapy on the processes of bone formation significantly differ.Objective: to study the effect and mechanism of action of shock wave therapy on the processes of reparative osteogenesis in an experiment and the effect of the method on delayed union of bone fractures and pseudarthrosis in clinical conditions.Materials and Methods. In an experiment on rabbits, after a standard model of a perforated defect in the proximal tibial metadiaphysis on the days 3, 6, 9, and 12 after injury; the injury site of the animals of the main group was influenced with radial low-energy shock waves. The results of treatment were monitored with the help of clinical, radiological and histomorphological methods. The clinical section included 136 patients with union fracture disorder of long bones who had previously undergone conservative treatment or osteosynthesis. All patients underwent 1-3 sessions of extracorporeal shock wave therapy with evaluation of the results on 3, 6, and 12 months after treatment using the data of X-ray examinations and the Neer – Crantham – Shelton functional scale.Results. The studies showed that rabbits of the main group morphologically had a greater thickness and density of formed bone crossbars at the site of the proximal tibial metadiaphysis defect in a month after extracorporeal shock wave therapy, and after 45 days, a greater number of cases of restoration of its cortical layer was notified (p<0.05). Three months after treatment of patients with delayed union of bone fractures with extracorporeal shock wave therapy, consolidation was detected radiologically in 89.4% of cases; this indicator remained almost unchanged in the subsequent periods of the study. Three months after treatment of patients with pseudoarthrosis of the bones with extracorporeal shock wave therapy, radiological consolidation was detected in 46.1% of patients, after 6 months – in 75.3%, after 12 months – in 80.9%. At the end of the study, scores on the Neer – Crantham – Shelton Functional Scale also improved significantly.Conclusions. The results of the studies allow us to conclude that extracorporeal shock wave therapy is an effective non-invasive method for the treatment of delayed union of bone fractures and pseudarthrosis and is an alternative to surgical interventions.